Palliative Care in Children With Advanced Heart Disease in a Tertiary Care Environment: A Mini Review - Bergsträsser, Eva; Lukose, Saumya; Zimmermann, Karin; Oxenius, Angela (Frontiers in Cardiovascular Medicine, 2022)
Palliative care for children continues to evolve. More recently, this has also been true in the field of pediatric cardiology, particularly for children with advanced heart disease. In these children, similarly to children with cancer, treatment successes are offset by the risks of long-term morbidities, including premature death. This mini review aims to provide an overview of current knowledge on children suffering from advanced heart disease, their medical care during various phases of illness (including the palliative and end-of-life phase), symptom burden, experiences of parents, prognostic understanding of parents and physicians, and current status of the involvement of pediatric palliative care. In conclusion, the suffering of these children at the end of their young lives is pronounced and many parents feel prepared neither for medical problems nor for the child’s death. An effective and mutually trusting partnership between pediatric cardiology and pediatric palliative care would appear to be a prerequisite for the timely involvement of palliative care in further supporting these children and their families.